Position of the Mental Foramen in a Northern Regional Palestinian Population - Ziyad K Mohammad; Rola Shadid; Mohamad Kaadna; Ala Qabaha; Abu-Hussein Muhamad (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2016)
Background: The mental foramen is one of important anatomical features frequently encountered in maxillofacial surgical procedures in premolars area. Its position has been shown to vary according to race. In this study researchers aim to study the position, shape, and appearance of the mental foramen, as seen on panoramic radiographs of Palestinians, and to compare our findings with international values. Materials and methods: A randomly selected panoramic radiographs (368 with 736 sides) from the records of dental patients attending three dental services in north of Palestine, the mental foramina's anterior-posterior position, shape, and radiologic appearance were subjected to analysis. Results: The most frequent anterior-posterior position was in the area between the long axes of first and second mandibular premolar teeth. The most frequent appearance was the continuous type and majority of foramina were rounded in shape. Conclusion: The position of the mental foramen on panoramic radiographs in this selected group of Palestinians was most commonly between the mandibular premolars. The continuous type and rounded shape of the mental foramen was founded in majority of cases. These results are similar to previous findings in Caucasian populations.